Sosialisasi Akuntansi Perpajakan Bagi Siswa SMK Jurusan Akuntansi - Sriyuniati, Fera (Jurusan Akuntansi Politeknik Negeri Padang, 2019)
Tax accounting is a part of important competence for an accounting student.The purpose of tax accounting is to set the outstanding tax according to the financial reports. There are many accounting teachers and students of accounting in secondary schools who do not understand tax accounting. The cause of all that is the lack of tax accunting literatures, the lack of understanding of tax accounting itself and practice tax case that are less varied. The purpose of this service is to provide a tax accounting for accounting teachers and students ranging from counting to reporting tax itself. The workshop targets are accounting teachers and students of SMKN 2 Padang. Workshop activities are providing training in tax accounting, making a simplified tax accounting module and making various tax accounting cases. The expectation results from this service are the existence of targets who understand and are skilled in tax accounting.